Color, Structure, and Thermal Stability of Alginate Films with Raspberry and/or Black Currant Seed Oils - Jolanta Kowalonek; Bogna Łukomska; Aleksandra Szydłowska-Czerniak (Molecules)
In this study, biodegradable and active films based on sodium alginate incorporated with different concentrations of oils (25% and 50%) from fruit seeds were developed for potential applications in food packaging. The ultraviolet and visible (UV-VIS) spectra of raspberry seed oil (RSO) and black currant seed oil (BCSO) indicated differences in bioactive compounds, such as tocopherols, phenolic compounds, carotenoids, chlorophyll, and oxidative status (amounts of dienes, trienes, and tetraenes) of active components added to alginate films. The study encompassed the color, structure, and thermal stability analysis of sodium alginate films incorporated with RSO and BCSO and their mixtures. The color of alginate films before and after the addition of oils from both fruit seeds was evaluated by measuring color coordinates in the CIELab color space: L* (lightness), a* (red-green), and b* (yellow-blue). The lightness values ranged between 94.21 and 95.08, and the redness values varied from −2.20 to −2.65, slightly decreasing for the films enriched with oils. In contrast, yellowness values ranged between 2.93 and 5.80 for the obtained active materials, significantly increasing compared to the control alginate film (L* = 95.48, a* = −1.92, and b* = −0.14). Changes in the structure and morphology of the alginate films after incorporating bioactive-rich oils were observed using scanning electron microscopy (SEM). Films with RSO and oil mixtures had more developed surfaces than films with BCSO. Moreover, the cross-sections of the films with RSO showed holes evenly distributed inside the films, indicating traces of volatile compounds. Thermal decomposition of the alginate films loaded with oils showed five separate stages (to 125 °C, 125–300 °C, 310–410 °C, 410–510 °C, and 750–1000 °C, respectively) related to the oil and surfactant decomposition. The shape of the thermogravimetric curves did not depend on the oil type. The added oils reduced the efficiency of alginate decomposition in the first stage. The obtained results showed that new functional and thermally stable food packaging films based on sodium alginate with a visual appearance acceptable to consumers could be produced by utilizing oils from fruit seed residues.